Steam Gasification of Crude Glycerin in a Packed Bed Reactor. Issue 4 (3rd May 2016) - Barata, P.; Veríssimo, A. S.; Costa, M.
ABSTRACT: Steam gasification of crude glycerin was carried out in a laboratory packed bed reactor and the effects of the bed temperature and flow rate of glycerin on the yields and characteristics of the syngas produced were examined. The tests were performed at bed temperatures of 700°C, 800°C, and 900°C over a wide range of water to glycerin ratios (W/G) using aluminum oxide as a packing material. Subsequently, the influence of the glycerin flow rate was studied at a fixed bed temperature of 800°C and a W/G of 4. The main conclusions are: (1) as the bed temperature increases, the hydrogen and carbon dioxide contents increase, the carbon monoxide and methane contents decrease, the heating value of the syngas produced slightly reduces, and the syngas production augments; (2) the glycerin flow rate does not influence the syngas production nor its heating value up to a certain value beyond which the production drops and the heating value increases a little; and (3) the minimum water content required for steam gasification to take place without reactor blocking decreases as the bed temperature increases, and increasing the glycerin flow rate increases the risk of bed deposition for the same W/G ratio.